The Levels of Thinking Skills in The Reading Comprehension Questions Given by the English Teachers of The Senior High Schools - Agnes Santi Widiati (Widya Mandala Surabaya Catholic University, 2012)
The goal of teaching English at the senior hIgh school is to enable students to use English for communication, both oral and written. The focus of the English classes is on the needs for being able to read in English. Reading activity is regarded as a complex process; and thus, requires the manipulation of more high-order thinking skills than low-order thinking skills. Teachers commonly give reading comprehension questions to their students both as reading exercises and tests. This study aims at finding out the levels of thinking skills in the reading questions given by the English teachers of the senior high schools. The source of the data was the questions given by 5 English teachers. The findings show that 28.39% of the total number of the questions require students to use high-order thinking skills to answer them and 71.61% of the total number of questions require students to use low-order thinking skills. As a complex process, reading should not be seen as a linear progression of thinking skills. Hence, students should be trained to jump between various levels of thinking; this means that they should be trained to create meaning as a result of the negotiation between their schemata, the nature of the texts, the writers’ message, and other features of reading. In the reading class, teachers should provide students with various questions which require the manipulation of more high levels of thinking.